The Role of Social Media in Halal Tourism Advocacy: An Analysis of the Communication Strategy of the Ministry of Tourism and Islamic Political Actors - Setiawan, Anang; Fathani, Aqil Teguh; Adrian, Maisarah Mitra (Jurnal Pemerintahan dan Kebijakan (JPK), 2025)
This study aims to analyze the communication strategies of the Ministry of Tourism and Islamic political actors in advocating halal tourism policies through social media. This study employed a qualitative approach, collecting data from January to June 2025 through Instagram and X/Twitter uploads by the Ministry of Tourism and three Islamic political parties: PKS, PKB, and PPP. The data were analyzed using thematic content analysis techniques to identify narrative patterns, communication styles, and dominant platforms used. The results showed that the Ministry of Tourism relies on digital campaigns, which are dominated by infographics, promotional videos, and collaborations with influencers, to build a narrative of national identity and a Sharia economy. On the other hand, PKS is more active on Twitter, employing an ideological and religious communication style. PKB stands out on Instagram with a cultural and inclusive approach, while PPP adopts a pragmatic style that emphasizes technical achievements and cross-actor cooperation. These findings revealed that the audience segmentation, political orientation, and ideological identity of each actor significantly influence digital communication strategies for promoting halal tourism.